Experimental Study on Heating Performance and a Novel Calculation Method of Water Outlet Temperature Based on Air Source Transcritical CO2 Heat Pump System - Dai, Chen; Qin, Xiang (Frontiers in Energy Research, 2022)
As a natural refrigerant, CO2 can greatly improve the environmental protection of the heat pump system. Since there is no perfectly suitable heat transfer correlation for supercritical CO2 at present, the water outlet temperature of the transcritical CO2 heat pump system has not been predicted. To study the applications of transcritical CO2 heat pump systems in heating performance and hot water supply, a series of experiments are carried out by an air source transcritical CO2 heat pump test rig. The experimental results show that the main factors affecting outlet water temperature are the system COP, the discharge pressure, the compressor frequency, and the ambient temperature. Based on the experimental results, a dimensionless correlation equation on outlet water temperature is proposed by the Buckingham PI theorem. This equation can be used to calculate the outlet water temperature of the air source transcritical CO2 heat pump systems with different sizes, and the calculation accuracy can be maintained at 13% with experimental results. Finally, the influence factors of the gas cooler water outlet temperature are analyzed based on the novel calculation method. Therefore, this study provides a reference for the prediction of the water outlet temperature of the transcritical CO2 heat pump system.